A Survey of the Prevalence of Parentally Abused Children With Visual Impairment in Special Schools, Oyo State, Nigeria: Array - Abodunrin, Sunday Abimbola (New Trends in Psychology, 2021)
There is an increase at the rate at which children with visual impairment are being abused by their parent. The objective of the study is to examine why children with visual impairment were being abused by their parent and ascertain the level at which children with visual impairment were being abused by their parent. Survey research design was utillised in the study, with the use of 30 respondents including totally blind and low vision and the result was analysed using descriptive statistics of frequency count, percentages, mean and standard deviation. The result shows that the reasons for abusing children with visual impairment by their parents include; parents seeing their children as useless in the family, being excluded from domestic work, source of embarrassment, shame, etc. The findings also reveal that, there is a high level of childs abuse by parents of children with visual impairment in the study. The study therefore recommends that, parents of children with visual impairment should be advised on how to relate with their child s with visual impairmen